REVIEW OF ISLAMIC CRIMINAL LAW ON THE SETTLEMENT OF MOTORCYCLE EMBEZZLEMENT CASES THROUGH RESTORATIVE JUSTICE - Amri, Ilal; Sadi Is, Muhamad; Kasmarani, Yuli (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The settlement of motorcycle embezzlement cases that occur in the community is usually resolved through litigation, but as the times develop, the case is resolved through the restorative justice mechanism. However, not all cases of motorcycle embezzlement can be resolved through restorative justice mechanisms and whether there is a deterrent effect on the perpetrator after the case is resolved through restorative justice. The formulation of this research problem is: first, how to resolve motorcycle embezzlement cases through restorative justice, second, how to resolve motorcycle embezzlement cases through restorative justice according to the perspective of Islamic criminal law. The author uses normative legal research with qualitative data types, namely research by examining and describing the sources of data obtained through literature studies, and document studies. The data sources used in this study are primary, secondary and tertiary legal materials. The results of the study conclude that the settlement of motorcycle embezzlement cases through restorative justice can be carried out through several requirements in existing regulations in the criminal justice subsystem such as in the Police, Prosecutor's Office and the General Justice Environment. In the Police, it is regulated in Police Regulation No. 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice. The Prosecutor's Office is regulated in Prosecutor's Regulation No. 15 of 2020. And finally, the application of motorcycle embezzlement cases can also be resolved through restorative justice in the Court environment based on the Supreme Court Regulation of the Republic of Indonesia No. 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. In Islamic criminal law, motorcycle embezzlement cases can be resolved through restorative justice if there is forgiveness from the family and also the perpetrator compensates for the losses due to the criminal act he has harmed.